Facile Fabrication of a Continuous ZIF‐67 Membrane for Efficient Azeotropic Organic Solvent Mixture Separation. Issue 15 (3rd March 2023) - Sun, Hao; Wang, Fengkai; Li, Xiaoting; Caro, Jürgen; Meng, Hong; Wang, Naixin; An, Quan‐Fu
Abstract: Azeotropic organic solvent mixture separation is common in the chemical industry but extremely difficult. Zeolitic imidazolate framework‐67 (ZIF‐67) shows great potential in organic solvent mixture separation due to its rigid micropores and excellent stability. However, due to the fast nucleation rate, it is a great challenge to prepare continuous ZIF‐67 membrane layers with ultrathin thickness. In this study, a hydroxy salt layer with high inducible activity was synthesized as a precursor on different porous substrates to prepare ZIF‐67 membranes at room temperature. The precursor layer enables an intact ZIF‐67 membrane with an ultrathin thickness of 176±12 nm. The experimental and simulation results confirmed that the size sieving through the pore windows and the preferential adsorption of polar solvent molecules provide the ZIF‐67 membrane an unprecedented separation performance such as high separation factors and fluxes, for four types of azeotropic organic solvent mixtures. Abstract : To prepare zeolitic imidazolate framework (ZIF) membranes, an ultrathin hydroxy salt precursor layer with high reactivity was constructed in situ. Its excellent induction effect allowed the formation of a continuous and ultrathin ZIF‐67 membrane on various surfaces at room temperature. Due to its pore size and preferential adsorption of polar molecules, the membrane gave excellent separation of azeotropic organic solvent mixtures.